The Tradition of Seven-Night Maghrib and Isha Congregational Prayers at the Funeral Home: A Study of Pekalese Tribe of Bengkulu Province in the Perspective of Islamic Law - Indra Gunawan; Agung Prayitno; Mustopa, Mustopa; Nenan Juli; Zurifah Nurdin (SEAN Institute, 2025)
This study examines the tradition of performingcongregational prayers for seven consecutive nights at thehouse of the deceased in the Pekal ethnic community in Ipuh, Mukomuko, and its alignment with Islamic law. The practice, although not explicitly mandated in the Qur'an orHadith, is understood as a social and spiritual activity thatstrengthens community solidarity and provides collectiveprayers for the deceased. The research explores thecompatibility of this tradition with the principles ofmaqashid shariah, which aims to preserve the welfare of thecommunity, strengthen social bonds, and safeguard the faith. The analysis also considers the perspectives of classical andcontemporary Islamic scholars regarding innovations in religious practices, such as Wahbah al-Zuhaili'scategorization of bid'ah hasanah (good innovation) andbid'ah dhalalah (misguided innovation). The findings suggestthat the tradition can be considered a form of bid'ah hasanahas long as it does not conflict with the core principles ofIslam, providing an opportunity for cultural preservationwhile maintaining religious integrity. This paper concludesby emphasizing the importance of contextualized religiouspractices that can reinforce both individual spirituality andcommunity cohesion within the framework of Islamic teachings.